Information Asymmetries about Measurement Quality - Glover, Jonathan; Levine, Carolyn B. (Contemporary Accounting Research, 2019)
ABSTRACT This article studies contracts between a principal and an agent that are robust to information asymmetries about measurement quality. Our main result is that an information asymmetry about measurement quality not only reduces the usefulness of a given performance measure for stewardship purposes, it also qualitatively changes the way the performance measure is used if the information asymmetry is sufficiently large. We also study the manipulability of performance measures, assuming that poor measurement quality creates room for manipulation via selective (cherry‐picked) corrections by the agent. With known imperfect measurement quality, manipulability lowers the cost of providing incentives. Manipulability introduces overstatements only, while imperfect measurement introduces both overstatements and understatements. However, with an information asymmetry about measurement quality, manipulability can increase the cost of providing incentives, since there is now an induced information asymmetry about manipulability.